Design and Development of a Novel Multi wavelength Brillouin-Erbium Fiber Laser - Al-Mansoori, Mohammed Hayder (2004)
Multi-wavelength laser sources with constant wavelength spacing are of great interest in dense wavelength division multiplexing (DWDM) communication and sensors systems.As the transmission capacity of optical communication systems is approaching a few Tb/s through WDM method in recent years, multiwavelength generation technology becomes more important, considering that the complexity and the cost of the source will increase as the number of WDM channel increases.In this thesis, the design and development of a novel architecture of multi-wavelength Brillouin/Erbium fiber laser (BEFL) utilizing a linear cavity fiber loop technique is presented. Simultaneous and stable multiple wavelength lasing in a linear cavity have been achieved. The results are based completely on the experimental work. The requirement of internal feedback that is commonly used for multiple wavelengths Brillouin/Erbium fiber laser using a ring configuration is achieved by the proposed linear cavity design. This design used only a single 980 nm pump laser for its multiple wavelengths operation. Based on the design parameters namely; 980 nm pump power, Brillouin pump power, Brillouin pump wavelength and single mode fiber (SMF) the performance of a novel BEFL is presented in terms of threshold power, Stokes signal peak power, number of Stokes generated, stability of the Stokes and tuning range. Throughout this work, three lengths of SMF-fiber are used, 1.9 km, 8.8 km and 25 km.The optimization of Brillouin pump wavelength, power and Erbium gain led to a maximum possible number of Stokes. Twenty-two stable output laser lines with 10.88 GHz (0.088 nm) line spacing were obtained at 1558 nm that was the peak of Erbiumdoped fiber (EDF) gain. The injected Brillouin pump power into the 8.8 km SMF-fiber was set at 0.9 dBm and the EDF was pumped by 100 mW of 980 nm pump laser.The most efficient cascaded Brillouin Stokes operation occurred at the peak of Erbium gain centered on 1558 nm. The number of Stokes decreased as the Brillouin pump increased in the highest region of Erbium gain. On the contrary, the number of Stokes was proportional to the intensity of the Brillouin pump power outside this wavelength range. The best performance and conversion efficiency of Brillouin pump to the BEFL signal occurs at the lower levels of injected Brillouin pump power.A low threshold of 4 mW pump power with 2.3 mW launched Brillouin pump into the 8.8 km of SMF-fiber at 1558 nm was obtained. The tuning range of the Stokes signal must be taken into account both the Brillouin and EDF pump powers, at a fixed EDF pump power the Stokes signal can be tuned wider at a higher Brillouin pump power while higher EDF pump power produces smaller tuning range.